Low-shrinkage and anti-freezing high-performance concrete and preparation method thereof

By using high-erosion silicate cement, ultra-fine solid waste blends, and sustained-release anti-coagulant high-strength aggregates in road concrete in high-altitude road concrete, low-shrinkage anti-coagulant high-performance concrete is prepared, which solves the problems of insufficient anti-coagulant performance and complex preparation process in the existing technology, and achieves efficient and economical concrete preparation and excellent anti-coagulant effect.

CN119504202AActive Publication Date: 2025-02-25GUILIN UNIVERSITY OF TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411556403.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-25
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The prior art has insufficient anti-condensation ice performance of road concrete in high-altitude areas, and the preparation process is complex and costly, making it difficult to meet traffic safety and construction needs.

Method used

High-performance concrete with low shrinkage anti-glodge ice is prepared by using high-strength iron silicate cement, ultra-fine solid waste admixture, sustained-release anti-glodge ice high-strength aggregate and other raw materials, combined with high-efficiency admixture and fibers.

Benefits of technology

It realizes low-cost, simple preparation technology, high volume stability and excellent anti-icing effect. It is suitable for road construction in high-altitude areas, significantly improving traffic safety and construction efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides low-shrinkage and anti-freezing high-performance concrete and a preparation method thereof, and particularly relates to the technical field of high-performance cement-based materials. The low-shrinkage and anti-freezing high-performance concrete is prepared from the following raw materials: cement, a superfine solid waste admixture, sand, stones, a slow-release type anti-freezing high-strength aggregate, fibers, a high-efficiency additive and water. The superfine solid waste admixture is used for equivalently replacing part of cement, the solid waste-based slow-release anti-freezing high-strength aggregate is used for equivalently replacing part of sand, the concrete has the advantages of high waste residue utilization rate and low preparation cost, and meanwhile, the mechanical property, the volume stability, the freeze-thaw resistance and the anti-freezing capability of the concrete are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-performance cement-based materials, and more specifically relates to a low-shrinkage and anti-icing high-performance concrete and a preparation method thereof. Background Art

[0002] The climate in high-altitude cold regions is complex and changeable. In most areas, the temperature fluctuates significantly throughout the year. The annual average temperature is low, with more than 2 / 3 of the time below zero, and there is a lot of low-temperature rain and snow, which poses a huge challenge to the maintenance of road traffic facilities and the smoothness of traffic. Traffic safety is particularly important in cold seasons, especially during snowfall, frost and freezing rain in winter. When the road surface is icy, the friction coefficient between the road surface and the tire drops sharply, which can easily cause serious safety accidents and traffic jams. At the same time, most of the high-altitude cold regions are plateaus and mountains, with complex natural climatic conditions, difficult road traffic construction and maintenance, long construction period and high cost. For this reason, it is urgent to develop high-durability and anti-icing road concrete preparation technology.

[0003] Although the invention patent with application number 201710820393.4, "An anti-icing asphalt concrete layer and its construction method", proposes a construction method for an anti-icing asphalt concrete layer, it has the problems of narrow anti-icing temperature range and limited anti-icing effect. The invention patent with application number 201810327732.X, "Durable lightweight anti-icing thin-layer bridge deck pavement structure and its preparation method", proposes a preparation method for a durable lightweight anti-icing thin-layer bridge deck pavement structure, but has the defects of easy loss of anti-icing salt and poor anti-icing effect in the later stage. The invention patent with application number 202410133508.2, "A low-temperature ultra-fiber anti-icing modified asphalt concrete and its preparation method", proposes a preparation method for low-temperature ultra-fiber anti-icing modified asphalt concrete, but has the problems of complex production process and high manufacturing cost. Therefore, it is of great significance to provide a concrete with low cost, simple preparation process, high volume stability and excellent anti-icing effect. Summary of the invention

[0004] The purpose of the present invention is to provide a low shrinkage and anti-icing high-performance concrete and a preparation method thereof, so as to solve the problems existing in the above-mentioned prior art, and the concrete has the advantages of simple preparation process, convenient operation, low production cost, high strength, small shrinkage, good frost resistance and good anti-icing effect.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is to provide a low shrinkage and anti-icing high-performance concrete, comprising the following raw materials in parts by weight:

[0007] 100 parts of cement, 30-100 parts of ultra-fine solid waste admixture, 80-150 parts of sand, 190-360 parts of gravel, 80-150 parts of slow-release anti-ice high-strength aggregate, 0.5-3 parts of fiber, 0.2-2 parts of high-efficiency admixture and 30-70 parts of water.

[0008] Preferably, the cement comprises high-iron silicate cement, and the strength grade of the cement is ≥42.5; the ultrafine solid waste admixture comprises one or more of slag, nickel-iron slag, steel slag, fly ash and phosphorus slag; the specific surface area of ​​the ultrafine admixture is ≥700m 2 / kg, 7d activity index ≥75%, 28d activity index ≥95%; the particle size of the ultrafine solid waste admixture is 0.1-38μm.

[0009] Preferably, the sand includes river sand or machine-made sand; the particle size fineness modulus of the sand is 2.4 to 3; and the gravel is crushed stone with a continuous particle size of 5 to 20 mm.

[0010] Preferably, the method for preparing the slow-release anti-ice high-strength aggregate comprises the following steps:

[0011] S1: by-product gypsum, slag, refined slag and Portland cement are mixed and aged to obtain a dry mix;

[0012] S2: adding calcium formate, triethanolamine and water to the dry mixture, mixing and granulating to obtain spherical blanks; curing the spherical blanks twice to obtain high-strength micro-nanoporous aggregates;

[0013] S3: Immersing the high-strength micro-nanoporous aggregate in an acetate solution, allowing it to stand and carbonize in sequence, thereby obtaining the slow-release anti-icing high-strength aggregate.

[0014] In the preparation process of the slow-release anti-ice high-strength aggregate of the present invention, in the alkaline environment provided by silicate cement, the by-product gypsum and slag undergo hydration reaction to obtain sulphoaluminate aggregate with ettringite as the main mineral composition, the chemical activity of calcium formate and triethanolamine is used to stimulate the early strength of the aggregate, and the calcium sulfate solution is used for curing to promote the formation and growth of high-sulfur hydrated calcium sulphoaluminate (AFt), so as to prepare high-strength micro-nanoporous aggregate. At the same time, the refined slag can be carbonized under high humidity and high CO2 concentration, which promotes further densification of the aggregate surface, and finally forms a dense surface shell layer, thereby improving the ability of the aggregate to release brine slowly.

[0015] The slow-release anti-icing high-strength aggregate described in the present invention is a slow-release anti-icing high-strength aggregate with a core-shell structure having a dense shell layer and a loose core layer. The relatively loose core layer structure can ensure that the aggregate absorbs as much water and acetate as possible; the relatively dense shell layer structure helps to slow down the release rate of pre-absorbed water and acetate in the aggregate, increase internal curing consumption and prolong the anti-icing time.

[0016] Preferably, the by-product gypsum includes one or more of desulfurized gypsum, phosphogypsum, titanium gypsum and citric acid gypsum; the particle size of the by-product gypsum is 0.1 to 150 μm; the slag includes blast furnace slag powder; the particle size of the slag is 0.1 to 75 μm; the particle size of the refined slag is 0.1 to 75 μm.

[0017] More preferably, the by-product gypsum has an attached water content of ≤20wt%, a dry basis CaSO4·2H2O content of ≥80wt%; and the specific surface area of ​​the slag is ≥400m 2 / kg, 28d strength activity index ≥95%; the physical and chemical indicators of the refined slag are Al2O34-7wt%, CaO 26-30wt% and SiO225-32wt%, and the rest are other chemical components such as Fe2O3, MgO, Na2O, etc.

[0018] Preferably, the mass ratio of the by-product gypsum, slag, refined slag, Portland cement, calcium formate, triethanolamine and water is 5-9:1-4:0.5-2:0.2-1:0.05-0.5:0.01-0.1:1-3.

[0019] Preferably, the acetate solution is a mixed aqueous solution of potassium acetate and sodium acetate, and the mass fraction of the acetate solution is 20-40%.

[0020] More preferably, the mass ratio of potassium acetate to sodium acetate is 1-5:1-5.

[0021] Preferably, the mixing time is independently 2 to 30 minutes; the aging time is 24 to 48 hours; the particle size of the spherical blank is 0.125 to 9.5 mm; the temperature of the first of the two curings is 20 to 25°C, the relative humidity of the first curing is 90 to 98%, and the time of the first curing is 1 to 3 days; the second of the two curings is cured in a calcium sulfate solution, the temperature of the second curing is 25 to 40°C, and the time of the second curing is 7 to 14 days; the standing is negative pressure standing, and the standing time is 10 to 120 minutes; the carbonization conditions are: temperature 25 to 60°C, pressure 0.1 to 0.4 MPa, CO2 volume concentration 95 to 99%; time 1 to 8 hours.

[0022] More preferably, the aging is: wrapping with a film and placing for 24 to 48 hours.

[0023] Preferably, the fiber comprises copper-plated steel fiber, basalt fiber, polyacrylonitrile fiber or polyester fiber; and the length of the fiber is 3 to 9 mm.

[0024] Preferably, the high-efficiency admixture is mixed with polycarboxylate water-reducing agent, nano CSH gel and APEO surfactant in a mass ratio of 85-99.8:0.1-10:0.1-5; the high-efficiency admixture composed of polycarboxylate water-reducing agent, nano CSH gel and APEO surfactant not only has excellent water-reducing effect, but also can significantly improve the early strength of concrete.

[0025] In the low shrinkage and anti-icing high-performance concrete of the present invention, when the internal humidity of the concrete gradually decreases with the progress of hydration, the pre-absorbed water in the slow-release anti-icing high-strength aggregate gradually seeps out, which plays an internal curing effect, can maintain the internal humidity of the concrete, and reduce the shrinkage of the concrete; when the concrete surface is under pressure, the pre-absorbed acetate in the slow-release anti-icing high-strength aggregate can seep out under the action of capillary pressure and partially enter the concrete surface, which can prevent the surface and interior of the concrete from freezing and improve the anti-icing performance of the concrete.

[0026] The second technical solution of the present invention is to provide a method for preparing the low shrinkage and anti-icing high-performance concrete, comprising the following steps:

[0027] According to the raw material ratio of the low shrinkage and anti-icing high-performance concrete, cement, ultra-fine solid waste admixture, sand, gravel, slow-release anti-icing high-strength aggregate and fiber are mixed, and high-efficiency admixtures and water are added thereto for mixing, and the low shrinkage and anti-icing high-performance concrete is obtained through molding and curing in sequence.

[0028] Preferably, the curing conditions are: temperature 20-25° C., relative humidity 90-98%.

[0029] The present invention discloses the following technical effects:

[0030] 1. The present invention utilizes high-iron silicate cement and ultrafine solid waste admixture as cementitious materials to prepare low-shrinkage and anti-icing high-performance concrete, which has the characteristics of low carbon emissions and green environmental protection.

[0031] 2. Compared with the technical solution in the prior art that uses cement alone as the cementitious material, the present invention uses cement and ultra-fine solid waste admixtures as cementitious materials, and uses ultra-fine solid waste admixtures to replace 23% to 50% of cement; at the same time, compared with the technical solution in the prior art that uses sand and gravel as aggregates, the present invention uses solid waste-based slow-release anti-icing high-strength aggregates, sand and gravel as aggregates, and uses solid waste-based slow-release anti-icing high-strength aggregates to replace 34.8% to 65.2% of sand, which has the advantages of high waste residue utilization and low preparation cost.

[0032] 3. The present invention utilizes high-iron silicate cement to reduce heat release and free water loss during the hydration process, utilizes ultra-fine solid waste admixtures to fill pores and improve the density of concrete, utilizes the slow-release water property of slow-release anti-icing high-strength aggregate to reduce concrete shrinkage, and utilizes the slow-release salt property of slow-release anti-icing high-strength aggregate to prevent freezing inside and on the surface of concrete, thereby improving the mechanical properties, volume stability, freeze-thaw resistance and anti-icing ability of concrete.

[0033] 4. The strength grade of the low shrinkage and anti-freezing high performance concrete prepared by the present invention is C40-C80, and the 56d shrinkage rate is ≤250×10 -6 , antifreeze grade ≥ F400, anti-icing temperature range is -20 ~ 0 ℃, with the characteristics of high strength, small shrinkage, good antifreeze and anti-icing effect. DETAILED DESCRIPTION

[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0035] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] The performance tests of the strength grade, 56d shrinkage rate, frost resistance grade and anti-icing temperature of the lightweight aggregate concrete described in the following embodiments and comparative examples are based on the following standards and methods: the 56d shrinkage rate and anti-icing grade of the concrete are tested using the "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete" GB / T50082-2009; the strength grade of the concrete is tested using the "Standard for Inspection and Evaluation of Concrete Strength" (GB / T50107-2010); the anti-icing temperature is determined by observing the freezing condition of the concrete, and the anti-icing temperature is tested using a differential scanning calorimeter.

[0040] The cement used in the following examples and comparative examples is high-iron silicate cement, and the strength grade of the cement is 42.5; the mineral composition and content of the cement are C3S28-45wt%, C2S 30-42wt%, C4AF 12-18wt%, C3A4-8wt%, and when the content of the cement mineral composition is less than 100%, other conventional mineral components such as Fe2O3, MgO, Na2O, etc. are also included.

[0041] The specific surface area of ​​the ultra-fine solid waste admixture used is ≥700m 2 / kg, 7d activity index ≥75%, 28d activity index ≥95%, particle size is 35μm; the ultrafine solid waste admixture used in Example 1 is slag, the ultrafine solid waste admixture used in Example 2 is steel slag, the ultrafine solid waste admixture used in Example 3 is nickel-iron slag, and the ultrafine solid waste admixture used in Example 4 is phosphorus slag;

[0042] The sand used is machine-made sand, and the particle size fineness modulus of the sand is 2.4;

[0043] The stones used are crushed stones with continuous particle size of 5 to 20 mm;

[0044] The fibers used were basalt fibers with a length of 5 mm;

[0045] The high-efficiency admixture used is a mixture of polycarboxylate water reducer, nano CSH gel and APEO surfactant in a mass ratio of 85:8:5;

[0046] The preparation steps of the slow-release anti-ice high-strength aggregate used are as follows:

[0047] S1: 80 parts of desulfurized gypsum (adherent water content ≤ 20wt%, dry basis CaSO4·2H2O content ≥ 80wt%, particle size 100μm), 30 parts of blast furnace slag powder (specific surface area ≥ 400m 2 / kg, 28d strength activity index ≥95%, particle size 75μm), 10 parts of refined slag (Al2O34-7wt%, CaO 26-30wt% and SiO225-32wt%, the rest are Fe2O3, MgO, Na2O and other chemical components) (particle size 75μm) and 5 parts of PO 42.5 silicate cement mix ratio are mixed, mixed in a mixer for 5-10min until mixed, and aged for 48h to obtain a dry mix;

[0048] S2: Add 3 parts of calcium formate, 1 part of triethanolamine and 15 parts of water to the dry mix and mix for 3 to 10 minutes until mixed, use a disc granulator to form spherical billets with a size of 1.25 to 5 mm, cure for 3 days under standard conditions, and then put into a saturated calcium sulfate solution at a temperature of 40°C for 10 days to obtain high-strength micro-nanoporous aggregates;

[0049] S3: Immerse the high-strength micro-nanoporous aggregate in a mixed aqueous solution of potassium acetate and sodium acetate with a weight fraction of 30% (the mass ratio of potassium acetate and sodium acetate is 1:5) and let it stand at negative pressure for 60 minutes. Then, put it into a carbonization reactor with a pressure of 0.2MPa, a temperature of 40°C, and a CO2 volume concentration of 95% and carbonize it for 5 hours to obtain a core-shell structured slow-release anti-icing high-strength aggregate with a dense shell layer and a loose core layer.

[0050] Embodiments 1 to 4

[0051] The raw materials and amounts used are shown in Table 1:

[0052] Table 1 Raw materials and dosage used in Examples 1 to 4

[0053] Example 1 Example 2 Example 3 Example 4 cement 100 copies 100 copies 100 copies 100 copies Ultrafine solid waste admixture 30 servings 45 servings 85 copies 100 copies Sand 80 servings 110 copies 135 copies 140 copies Stone 310 copies 270 copies 230 copies 190 copies Slow-release anti-ice high-strength aggregate 80 servings 95 copies 135 copies 150 copies fiber 2 servings 1.5 servings 1 serving 0.5 serving High efficiency admixture 1.4 servings 1 serving 0.6 parts 0.8 parts water 30 servings 40 servings 60 servings 70 servings

[0054] The preparation method is as follows:

[0055] According to the mix ratio of each raw material in Table 1, cement, ultrafine solid waste admixture, sand, gravel, slow-release anti-ice high-strength aggregate and fiber are added to the mixer in sequence and mixed for 10 minutes until mixed evenly, and then high-efficiency admixture and water are added and mixed for 5 minutes until mixed evenly to obtain a mixture; the mixture is cast in a mold and cast into shape, and then cured under standard conditions of a temperature of 20°C and a relative humidity of 95% to the corresponding age to obtain low shrinkage anti-ice high-performance concrete.

[0056] After testing, the strength grade of the low shrinkage and anti-freezing high performance concrete obtained in Example 1 is C50-C60, and the 56d shrinkage rate is 247×10 -6 , antifreeze grade ≥ F400, no ice on the concrete surface at temperature ≥ -7.3℃;

[0057] The strength grade of the low shrinkage and anti-freezing high performance concrete obtained in Example 2 is C70-C80, and the 56d shrinkage rate is 224×10 -6 , antifreeze grade ≥ F400, no ice on the concrete surface at temperature ≥ -11.2℃;

[0058] The strength grade of the low shrinkage and anti-freezing high performance concrete obtained in Example 3 is C60-C70, and the 56d shrinkage rate is 206×10 -6 , antifreeze grade ≥ F400, no ice on the concrete surface at temperature ≥ -15.5℃;

[0059] The strength grade of the low shrinkage and anti-freezing high performance concrete obtained in Example 4 is C40-C50, and the shrinkage rate at 56 days is 182×10 -6 , antifreeze grade ≥F400, no ice on the concrete surface under temperature ≥-19.6℃.

[0060] Comparative Examples 1 to 4

[0061] The raw materials and amounts used are shown in Table 2:

[0062] Table 2 Raw materials and dosage used in comparative examples 1 to 4

[0063] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 cement 100 copies 100 copies 100 copies 100 copies Ultrafine solid waste admixture 30 servings 45 servings 85 copies 100 copies Sand 160 copies 205 copies 270 copies 290 copies Stone 310 copies 270 copies 230 copies 190 copies fiber 2 servings 1.5 servings 1 serving 0.5 serving High efficiency admixture 1.4 servings 1 serving 0.6 parts 0.8 parts water 30 servings 40 servings 60 servings 70 servings

[0064] The preparation method is as follows:

[0065] According to the mix ratio of each raw material in Table 2, cement, ultrafine solid waste admixture, sand, gravel and fiber are added to the mixer in sequence and mixed for 10 minutes until mixed evenly, and then high-efficiency admixture and water are added and mixed for 5 minutes until mixed evenly to obtain a mixture; the mixture is cast in a mold and cast into shape, and then cured under standard conditions of a temperature of 20°C and a relative humidity of 95% to the corresponding age to obtain low shrinkage and anti-ice high-performance concrete.

[0066] After testing, the strength grade of the low shrinkage and anti-freezing high performance concrete obtained in Comparative Example 1 is C40, and the 56d shrinkage rate is 318×10 -6 , the antifreeze grade is F200, and the concrete surface freezes when the temperature reaches -2°C;

[0067] The strength grade of the low shrinkage and anti-freezing high performance concrete obtained in Comparative Example 2 is C60, and the 56d shrinkage rate is 337×10 -6 , antifreeze grade F200, the concrete surface freezes when the temperature reaches -2℃;

[0068] The strength grade of the low shrinkage and anti-freezing high performance concrete obtained in Comparative Example 3 is C50, and the 56d shrinkage rate is 304×10 -6, antifreeze grade F200, the concrete surface freezes when the temperature reaches -2℃;

[0069] The strength grade of the low shrinkage and anti-freezing high performance concrete obtained in Comparative Example 4 is C40, and the 56d shrinkage rate is 311×10 -6 , antifreeze grade F200, the concrete surface freezes when the temperature reaches -2℃.

[0070] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0071] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A low shrinkage and anti-icing high performance concrete, characterized in that: Including the following raw materials by mass: 100 parts of cement, 30-100 parts of ultra-fine solid waste admixture, 80-150 parts of sand, 190-360 parts of gravel, 80-150 parts of slow-release anti-ice high-strength aggregate, 0.5-3 parts of fiber, 0.2-2 parts of high-efficiency admixture and 30-70 parts of water.

2. The low shrinkage and anti-icing high performance concrete according to claim 1, characterized in that: The cement includes high-iron silicate cement, and the strength grade of the cement is ≥42.5; the ultra-fine solid waste admixture includes one or more of slag, nickel-iron slag, steel slag, fly ash and phosphorus slag; the specific surface area of ​​the ultra-fine admixture is ≥700m 2 / kg, 7d activity index ≥75%, 28d activity index ≥95%; the particle size of the ultrafine solid waste admixture is 0.1-38μm.

3. The low shrinkage and anti-icing high performance concrete according to claim 1, characterized in that: The sand includes river sand or machine-made sand; the particle size fineness modulus of the sand is 2.4 to 3; the gravel is crushed stone with a continuous particle size of 5 to 20 mm.

4. The low shrinkage and anti-icing high performance concrete according to claim 1, characterized in that: The preparation method of the slow-release anti-ice high-strength aggregate comprises the following steps: S1: by-product gypsum, slag, refined slag and Portland cement are mixed and aged to obtain a dry mix; S2: adding calcium formate, triethanolamine and water to the dry mixture, mixing and granulating to obtain spherical blanks; curing the spherical blanks twice to obtain high-strength micro-nanoporous aggregates; S3: Immersing the high-strength micro-nanoporous aggregate in an acetate solution, allowing it to stand and carbonize in sequence, thereby obtaining the slow-release anti-icing high-strength aggregate.

5. The low shrinkage and anti-icing high performance concrete according to claim 4, characterized in that: The by-product gypsum includes one or more of desulfurized gypsum, phosphogypsum, titanium gypsum and citric acid gypsum; the particle size of the by-product gypsum is 0.1 to 150 μm; the slag includes blast furnace slag powder; the particle size of the slag is 0.1 to 75 μm; the particle size of the refined slag is 0.1 to 75 μm.

6. The low shrinkage and anti-icing high performance concrete according to claim 4, characterized in that: The mass ratio of the by-product gypsum, slag, refined slag, silicate cement, calcium formate, triethanolamine and water is 5-9:1-4:0.5-2:0.2-1:0.05-0.5:0.01-0.1:1-3; the acetate solution is a mixed aqueous solution of potassium acetate and sodium acetate, and the mass fraction of the acetate solution is 20-40%.

7. The low shrinkage and anti-icing high performance concrete according to claim 4, characterized in that: The mixing time is independently 2 to 30 minutes; the aging time is 24 to 48 hours; the particle size of the spherical blank is 0.125 to 9.5 mm; the temperature of the first curing of the two curings is 20 to 25°C, the relative humidity of the first curing is 90 to 98%, and the time of the first curing is 1 to 3 days; the second curing of the two curings is curing in a calcium sulfate solution, the temperature of the second curing is 25 to 40°C, and the time of the second curing is 7 to 14 days; the standing is negative pressure standing, and the standing time is 10 to 120 minutes; the carbonization conditions are: temperature 25 to 60°C, pressure 0.1 to 0.4 MPa, CO2 volume concentration 95 to 99%; time 1 to 8 hours.

8. The low shrinkage and anti-icing high performance concrete according to claim 1, characterized in that: The fiber comprises copper-plated steel fiber, basalt fiber, polyacrylonitrile fiber or polyester fiber; the length of the fiber is 3-9 mm; the high-efficiency admixture is prepared by mixing polycarboxylate water reducer, nano CSH gel and APEO surfactant in a mass ratio of 85-99.8:0.1-10:0.1-5.

9. The method for preparing the low shrinkage and anti-icing high performance concrete according to any one of claims 1 to 8, characterized in that: The steps include: According to the raw material ratio of the low shrinkage and anti-icing high-performance concrete, cement, ultra-fine solid waste admixture, sand, gravel, slow-release anti-icing high-strength aggregate and fiber are mixed, and high-efficiency admixtures and water are added thereto for mixing, and the low shrinkage and anti-icing high-performance concrete is obtained through molding and curing in sequence.

10. The method for preparing the low shrinkage and anti-icing high performance concrete according to claim 9, characterized in that: The curing conditions are: temperature 20-25° C., relative humidity 90-98%.

Citation Information

Patent Citations

  • Anti-icing asphalt concrete layer and construction method thereof

    CN107524066A

  • Durable lightweight anti-icing thin-layer bridge deck pavement structure and its preparation method

    CN108301321B

  • Low-temperature microfiber ice-coagulation-resistant modified asphalt concrete and preparation method thereof

    CN118005319A

  • Steel fiber reinforced ultra-high-performance concrete synergistically prepared by multiple solid waste and preparation method of steel fiber reinforced ultra-high performance concrete

    CN110423081A

  • Slow-release type anti-freezing high-strength pervious concrete and preparation method thereof

    CN113603420A